Perioperative anaphylaxis in children: A report from the Wake‐Up Safe collaborative. Issue 2 (4th January 2021) - Wakimoto, Mayuko; Miller, Rebecca; Kim, Stephani S.; Uffman, Joshua C.; NafiuS, Olubukola O.; Tobias, Joseph D.; Beltran, Ralph J.
Abstract: Background: Anaphylactic reactions to antigens in the perioperative environment are uncommon, but they have a potential to lead to serious morbidity and/or mortality. The incidence of anaphylactic reactions is 1:37 000 pediatric anesthetics, and substantially less than the 1:10 000 to 1:20 000 incidence in the adult population. Neuromuscular blocking agents, latex, and antibiotics are the most frequently cited triggers. To date, there is no comprehensive report on perioperative anaphylactic reactions in children in the United States. Using the Wake‐up Safe database, we examined the incidence and consequences of reported perioperative anaphylaxis events. Methods: We reviewed the Wake‐up Safe database from 2010 to 2017 and identified all reported instances of anaphylaxis. The triggering agent, timing, and location of the registered event, severity of patient harm, and preventability were identified. Narrative review of free‐text comments entered by reporting centers was performed to determine presenting symptoms, and interventions required. Type of case was identified from procedure codes provided in mandatory fields. Results: Among 2 261 749 cases reported to the Wake‐up Safe database during the study period, perioperative anaphylactic reactions occurred in 1:36 479 (0.003%). Antibiotics, neuromuscular blocking agents, and opioid analgesics were the main triggers. Forty‐nine cases (79%) occurred in the operating room, and 13 cases (21%) occurred in off‐site locations. Seven (11%) patients required cardiopulmonary resuscitation following the onset of symptoms. Thirty‐five (57%) patients were treated with epinephrine or epinephrine plus other medications, whereas 5% were managed only with phenylephrine. Most cases (97%) required escalation of care after the event. Regarding case preventability, 91% of cases were marked as either "likely could not have been prevented" or "almost certainly could not have been prevented." Conclusion: The estimated incidence of anaphylaxis and inciting agents among the pediatric population in this study were consistent with the most recent published studies outside of the United States; however, new findings included need for cardiopulmonary resuscitation in 11% of cases, and estimated fatality of 1.6%. The management of perioperative anaphylaxis could be improved for some cases as epinephrine was not administered, or its administration was delayed. Fewer than half of reported cases had additional investigation to formally identify the responsible agent.